2019
DOI: 10.1002/smtd.201900589
|View full text |Cite
|
Sign up to set email alerts
|

Microphysiological Systems: Next Generation Systems for Assessing Toxicity and Therapeutic Effects of Nanomaterials

Abstract: Nanomaterials (NMs) such as polymeric nanoparticles (NPs), vesicles, and dendrimers have revolutionized the biomedical field by enabling superior drug delivery, imaging, and sensing modalities. [1] The field of NMs is expected to grow tremendously as the nanotechnology market is projected to be worth $125 billion by 2024. [2] In addition, the increasing number of NMs used for diagnostic and therapeutic [3] purposes impose new restrictions on their intended effects and unwanted complications. We are continuousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 177 publications
(120 reference statements)
0
48
0
Order By: Relevance
“…[15] Precursory development of cell-based biosensors for drug and pathogen characterization opened the path for modeling the key functional units of organs in microfluidic platforms, later termed organ-on-chip (OoC). [15][16][17][18][19] Such platforms are aimed to reproduce the biological composition, function, and environment of native human tissue and bridge the gap between standard in vitro approaches and the human body. [20] This was demonstrated by reconstructing a physiologically relevant lung-on-a-chip capable of stretching and dynamically perfusing an alveolar-capillary interface model.…”
Section: The Role Of Skin In the Human Body Is Indispensable Servingmentioning
confidence: 99%
See 1 more Smart Citation
“…[15] Precursory development of cell-based biosensors for drug and pathogen characterization opened the path for modeling the key functional units of organs in microfluidic platforms, later termed organ-on-chip (OoC). [15][16][17][18][19] Such platforms are aimed to reproduce the biological composition, function, and environment of native human tissue and bridge the gap between standard in vitro approaches and the human body. [20] This was demonstrated by reconstructing a physiologically relevant lung-on-a-chip capable of stretching and dynamically perfusing an alveolar-capillary interface model.…”
Section: The Role Of Skin In the Human Body Is Indispensable Servingmentioning
confidence: 99%
“…[9,19,20] However, their most powerful application comes when connected to multiple OoC devices to form a human-on-a-chip for assessing system-wide effects. [18] By more closely mimicking human tissue, SoC models promise true predictive abilities capable of limiting the number of drugs that successfully passed preclinical testing only to fail in clinical trials, and reducing the risk of eliminating drugs that are unsuccessful in animals but may be effective in humans. In this Review, a brief introduction to the anatomy and physiology of human skin with the view of highlighting key aspects that are required of a biomimetic skin model is provided, before discussing the current state-of-the-art fabrication techniques.…”
Section: The Role Of Skin In the Human Body Is Indispensable Servingmentioning
confidence: 99%
“…For instance, the high surface-to-volume ratio of nanoparticles makes them highly reactive when compared to bulk materials (Recordati et al, 2015). Nanoparticles can penetrate cellular membranes, biological barriers and tissues, so they interact with biological systems at the molecular, cellular, organismal and ecosystem levels (Pietroiusti et al, 2018), The increasing interest of using nanoparticles in medicine, opens new possibilities for microtechnology, for instance to mimic whole organs (Organ-on-A-Chip technology), generating devices able to precisely study the effect of nanomaterials in a similar environment to in vivo (Ashammakhi et al, 2020).…”
Section: Nanotoxicologymentioning
confidence: 99%
“…Due to the high toxicity and barrier penetration capability of nanoparticles, the studies of their effects on three-dimensional environments, mimicking natural biosystems, enable more reliable approaches to evaluate the physiological effects of nanomaterials (Ashammakhi et al, 2020). For instance, Arends et al reported a microfluidic device to study the diffusion of nanoparticles through the basal layer, which is key to control the movement of nanoparticles between blood vessels and the surrounding extravascular space, observing a charge dependant accumulation of the species, similar to the one observed in vivo (Arends et al, 2015).…”
Section: Nanotoxicologymentioning
confidence: 99%
“…In vitro experiments fail to control the exposure levels of nanomaterials and cannot take into account some physicochemical aspects, such as particle aggregation. Ashammakhi et al (2020) have proposed that microphysiological systems, especially multiorgan-ona-chip systems, which can be specifically designed to test the systemic toxicity, can be of use to evaluate the toxicity of nanomaterials [122]. The potential of microfluidic systems is evaluated for nanotoxicity research in various experiments.…”
Section: Liver Skinmentioning
confidence: 99%